The great slowdown and political populism - Gylfi Zoega (EconPol Forum, 2024)
Populism embeds truth in a welter of lies. Populism erodes trust in mainstream political parties, institutions, ideas, and ideologies. Stagnating productivity, large trade imbalances, and waves of immigration have contributed to increased discontent in the West and eroded trust. Inclusive growth would lift all boats and rebuild trust. Populist policies are an impediment to such growth.
Keywords: 330